MOF-driven ultra-small hollow Co9S8 nanoparticles embedded in porous carbon for lithium-ion batteries. Issue 10 (8th May 2018) - Zhang, Liugen; Li, Hui; Xie, Hongtao; Chen, Tingxiang; Yang, Chao; Wang, Jide
Abstract: Abstract : Uniformly dispersed ultra-small hollow Co9 S8 nanoparticles (<10 nm) (H-Co9 S8 @C) and solid Co9 S8 nanoparticles (S-Co9 S8 @C) in porous carbon were fabricated separately by solvothermal and sulfur powder sulphurisation using Co-MOF-74 as the template. Owing to significant structural stability and uniform hollow structure of carbon-encapsulated Co9 S8, the as-prepared H-Co9 S8 @C exhibited excellent lithium ion storage performance as an anode material. Worked in the voltage of 0.01–3.0 V, H-Co9 S8 @C revealed outstanding rate capability (850, 670, 613, 552, 457, and 347 mA h/g at 0.1, 0.2, 0.5, 1, 2, and 3 A/g, respectively), and high reversible capacity (after 250 cycles with a remained capacity of 900.5 mA h/g). Compared with S-Co9 S8 @C, over 50 cycles, the discharge specific capacity of H-Co9 S8 @C was still maintained at 655 mA h/g at a current density of 0.5 A/g, whereas the capacity of S-Co9 S8 @C declined rapidly to 160.4 mA h/g. The results showed that superior capacity, excellent rate performance, and highly stable cycle performance depended mainly on the hollow characteristic of Co9 S8 .